PENGARUH STRATEGI PDR TERHADAP ACTIVE LEARNING DAN KEMAMPUAN BEKERJASAMA ANAK USIA DINI - ayu asmah; yulianti yulianti (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2016)
ABSTRACT The  aim  of  this  paper  is  to  know  the  effect  of  Plan  Do  Review  (PDR)on  early childhood  students’  active  learning  and  ability  to  cooperate.  Quantitative  design  used  in this  research  with  nonequivalent  control  group  design.  The  data  were  gathered  through observation  and  documentation.  The  gathered  data  were  analyzed  using  ANOVA  and MANOVA.  The  findings  showed  that  (1)  test  result  of  PDR  strategy  (variable  X)  on  active learning (variable Y1) has  significant effect  at level 0.04 < 0.05 ; (2) the test result of PDR strategy on  ability to cooperate variable (Y2) has significant effect  at level 0.06 < 0.05; (3) test  result  using  Hottelling’s  trace  of  PDR  strategy  on  active  learning  and  ability  to cooperate  showed  significant  at  level  0.001  <  0.05.  It  is  suggested  for  the  early  childhood institution  to  promote  learning  through  student  centered  approach,  teacher  should  more creative  and  innovative  in  developing  learning  that  suitable  with  the  students  needs  and interests.  Keywords:  PDR strategy; active learning; cooperate ability